2012
DOI: 10.1038/leu.2012.309
|View full text |Cite
|
Sign up to set email alerts
|

Extensive bone marrow infiltration and abnormal free light chain ratio identifies patients with asymptomatic myeloma at high risk for progression to symptomatic disease

Abstract: Asymptomatic multiple myeloma (AMM) is characterized by a constant risk of progression to symptomatic myeloma. To evaluate previously recognized risk factors and to identify high-risk features we analyzed 96 patients with AMM and at least 18 months of follow-up. The progression rate at 1,2, and 3 years was 8%, 15% and 26%, respectively, and the projected 5-year progression rate was 38%. Extensive bone marrow (BM) infiltration, abnormal free light chain (FLC) ratio and serum monoclonal (M)-protein ≥ 3 gr/dl wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
97
2
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 24 publications
10
97
2
2
Order By: Relevance
“…Pérez‐Persona et al 30 identified immunoparesis as a significant risk factor for progression and included this parameter in a risk model for patients with smoldering myeloma 31. On the contrary, immunopareresis could not be confirmed as risk factor for progression by the Greek myeloma group 32. Similar discrepancies apply to patients with active myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Pérez‐Persona et al 30 identified immunoparesis as a significant risk factor for progression and included this parameter in a risk model for patients with smoldering myeloma 31. On the contrary, immunopareresis could not be confirmed as risk factor for progression by the Greek myeloma group 32. Similar discrepancies apply to patients with active myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…This includes patients with SMM who have an involved/uninvolved serum free light-chain (FLC) ratio in excess of 100 who are at a high risk for myeloma and light-chain cast nephropathy [18,19]. When multiple myeloma is suspected clinically, patients should be tested for the presence of M proteins using a combination of tests that should include a serum protein electrophoresis (SPEP), serum immunofixation (SIFE), and the serum FLC assay [20].…”
Section: Poems Syndromementioning
confidence: 99%
“…In multivariate analysis, a highly abnormal (> 100) FLC ratio and a BM infiltration of over 60% were the only independent risk factors for progression with an HR of 9 (95%CI: 2.15-39) and 13 (95%CI: 4.42-42.2), respectively (illustrated in Figure 1A). 34 The Heidelberg group investigated the prognostic significance of WB-MRI in SMM and retained the presence of focal lesions on WB-MRI as the strongest adverse prognostic factor for progression to symptomatic MM. Multivariate analysis of the MRI and non-MRI parameters revealed that the presence and the number of focal lesions (HR: 3.01), as well as a diffuse bone marrow infiltration in MRI (HR: 2.37), remained the only significant prognostic factors for progression (illustrated in Figure 1A).…”
Section: Smoldering Myelomamentioning
confidence: 99%
“…33 This group investigated the prognostic value of several laboratory and radiological examinations and identified myeloma cell infiltration, the M-protein levels, free light chain (FLC) ratios and the MRI pattern as risk factors for progression. 34 In their study, the hazard ratio (HR) for patients with an abnormal MRI was calculated at 5.8 (1.84-18.35), and 5 of 8 patients with abnormal MRI progressed within 18 months. In multivariate analysis, a highly abnormal (> 100) FLC ratio and a BM infiltration of over 60% were the only independent risk factors for progression with an HR of 9 (95%CI: 2.15-39) and 13 (95%CI: 4.42-42.2), respectively (illustrated in Figure 1A).…”
Section: Smoldering Myelomamentioning
confidence: 99%